Effect of polyethylene-graft-maleic anhydride (PE-g-MAH) as compatibilizer on thermal properties and XRD characterization of low density polyethylene/natural rubber/water hyacinth fiber (Eichhornia Crassipes) composites. - Tan, Soo Jin (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.